Enlightenment Against Ignorance - Kurbanov Zuhriddin; Safoyeva Sevara Sokhibovna; Turaev Abrar Salokhiddinovich (Zien Journals, 2022)
This article is an imitation of the idea that the backwardness of science and enlightenment is the struggle against ignorance, the path chosen by independent Uzbekistan, that is, "The struggle against ignorance should be fought only with enlightenment."
Keywords: Enlightenment from backwardness to ignorance; Eastern Renaissance; Enlightenment; Jaded